2019
DOI: 10.1016/j.isci.2018.12.023
|View full text |Cite
|
Sign up to set email alerts
|

A Tet/Q Hybrid System for Robust and Versatile Control of Transgene Expression in C. elegans

Abstract: SummaryBinary gene regulatory tools such as the Tetracycline (Tet)-controlled transcription system have revolutionized genetic research in multiple organisms, but their applications to the worm remain very limited. Here we report that the canonical Tet system is largely inactive in the worm but can be adapted for the worm by introducing multiple modifications, a crucial one being the use of the transcription activation domain from the fungal Q binary system. The resultant Tet/Q hybrid system proves more robust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 50 publications
0
29
0
Order By: Relevance
“…Δpes-10 , the minimal promoter of the worm gene pes-10 , was shown to support strong gene expression in C. elegans [ 19 , 20 ]. We constructed a Δpes-10 -containing DNA substrate, PESDNA, that is structurally similar to the CMV-containing substrate HNDNA (Table S 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Δpes-10 , the minimal promoter of the worm gene pes-10 , was shown to support strong gene expression in C. elegans [ 19 , 20 ]. We constructed a Δpes-10 -containing DNA substrate, PESDNA, that is structurally similar to the CMV-containing substrate HNDNA (Table S 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that, like in mammals, the CMV promoter can drive gene expression in C. elegans . Mao et al reported that the Tetracycline (Tet)-controlled transcription system, which contains the CMV minimal promoter, is largely inactive in C. elegans [ 20 ]. This could be due to the competitive binding of unknown factors in C. elegans to the Tet operator sequences upstream the CMV promoter, which would interfere with the binding of the activator rTetR-VP16 to the same sequences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By restricting the expression of tTA or rtTA to a tissue or cell type of interest and adding Tet or Dox at a specific time point, these systems allow for both spatial and temporal control of gene (in)activation. The technique has limited use in C. elegans owing to the canonical Tet system being mostly inactive in the nematode (Mao et al, 2019), but has been applied more often in D. melanogaster, since its first use in these fruit flies in 1998 (Bello et al, 1998;Bieschke et al, 1998). Beyond these two leading invertebrate models, Tet systems have also been applied in diverse insect species, such as the malaria mosquito Anopheles stephensi (Lycett et al, 2004) and the silkworm B. mori (Karasaki et al, 2009;Tatsuke and Lee, 2013), and tTA-EGFP vectors have been designed for future applications in a wide range of insect species (Hara et al, 2008(Hara et al, , 2009.…”
Section: Tetracycline-controlled Transcriptional Activation Depends On Small Molecules For Temporal Controlmentioning
confidence: 99%
“…An additional development is the combination of the Tet system with Gal4-UAS ), as will be further considered when discussing combinatorial techniques later in this manuscript. Only recently has the system been adapted for application in C. elegans, when used in combination with the Q system (Mao et al, 2019), as will also be discussed in more detail in the section on combinatorial approaches.…”
Section: Tetracycline-controlled Transcriptional Activation Depends On Small Molecules For Temporal Controlmentioning
confidence: 99%